Asuhan Keperawatan Gangguan Eliminasi Urin pada Ny. K dengan Infeksi Saluran Kemih di Ruang Ar-Rahman RSI Purwokerto: Nursing Care of Urinary Elimination Disorders in Mrs. K with Urinary Tract Infection in the Ar-Rahman Room RSI Purwokerto - Rahmawati, Oktaviani Nur; Tri Y, Danang; Suandika, Made (Journal of Nursing Education and Practice, 2023)
Introduction: Urinary tract infection (UTI) or Urinarius Tractus Infection is a condition where there is a bacterial infection of microorganisms that occurs in the urinary tract.  The occurrence of UTI is due to the presence of pathogenic microorganisms in the urinary tract. These microorganisms enter through direct contact from the nearest place of infection, hematogenous, or lymphogenous.  Symptoms of UTI are the desire to urinate that continues to be felt, pain or sensation of heat when urinating (this set of conditions is called anyang-anyang), turbid and sharp-smelling urine, frequent urination, bloody or purulent urine, in women generally the patient will feel pelvic pain, especially in the pelvic center and the bone area around the genitals. Objectives: To describe nursing care in urinary tract infection patients who have impaired urinary elimination. Method: This research uses qualitative descriptive methods in the form of case studies. Nursing care was given to Mrs. K for 3 days. Data collection techniques obtained from the results of interviews, observations, and physical examinations. Result: The problem of urinary elimination disorders that occur in urinary tract infection patients can be overcome by conducting deep breath relaxation therapy to reduce the pain experienced by the patient training the patient not to hold urination, and advising the patient to increase the frequency of drinking.  The results obtained after the nursing action show the patient's pain gradually decreases, and the frequency of urination is smooth even though it still feels pain when urinating. Conclusion: After nursing treatment for 3x24 hours, the problem of urinary elimination disorders gradually improved characterized by an improved elimination pattern of decreased patient pain complaints.